2017
DOI: 10.14740/jocmr3046e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Apolipoprotein E Gene Polymorphism and Blood Lipid Level in Hemodialysis Patients

Abstract: BackgroundThe aim was to investigate the clinical characteristics of lipid metabolism and the effect of apolipoprotein E (ApoE) gene polymorphism on lipid metabolism in hemodialysis patients.MethodsThe serum levels of total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDLC), low-density lipoprotein cholesterol (LDLC), ApoA1, ApoB, ApoE and lipoprotein Lp(a) were detected by polymerase chain reaction-restriction fragment length (PCR-RFLP).ResultsThe level of serum TG was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Guz et al (2000) indicated that the ApoE polymorphism significantly affected serum levels of TC and LDL-C in HD patients, but was not associated with the presence of atherosclerosis in these individuals (Guz et al, 2000). Wang et al (2003) suggested that HD patients were liable to develop hypertriglyceridemia and hypocholesterolemia. The TG level might be related to the development of CVD in HD patients, whereas the patients with the allele of ApoE e4 were liable to develop dyslipidemia (Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guz et al (2000) indicated that the ApoE polymorphism significantly affected serum levels of TC and LDL-C in HD patients, but was not associated with the presence of atherosclerosis in these individuals (Guz et al, 2000). Wang et al (2003) suggested that HD patients were liable to develop hypertriglyceridemia and hypocholesterolemia. The TG level might be related to the development of CVD in HD patients, whereas the patients with the allele of ApoE e4 were liable to develop dyslipidemia (Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2003) suggested that HD patients were liable to develop hypertriglyceridemia and hypocholesterolemia. The TG level might be related to the development of CVD in HD patients, whereas the patients with the allele of ApoE e4 were liable to develop dyslipidemia (Wang et al, 2003). Liberopoulos et al (2004) observed that the ApoE concentration in combination with the ApoE polymorphisms significantly influenced serum lipid parameters in HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact pathophysiology of HD is still unclear. Recently, accumulated evidences suggest that the serum apolipoprotein E ( ApoE ) genetic variants and concentration play important functions for the development of HD [1–3,5,10–18]. The ApoE gene has been considered as one of the most important candidate genes for affecting the risk of HD [1,2,5,10–12,15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulated evidences suggest that the serum apolipoprotein E ( ApoE ) genetic variants and concentration play important functions for the development of HD [1–3,5,10–18]. The ApoE gene has been considered as one of the most important candidate genes for affecting the risk of HD [1,2,5,10–12,15,16] . ApoE gene, located on chromosome 19q13.2, is a polygenetic gene, and single‐nucleotide polymorphisms (SNPs) of ApoE gene could influence the expression and function of ApoE protein, which are potentially associated with the risk of HD and are contributing to affect the prognosis of HD patients [1,2,5,10,11].…”
Section: Introductionmentioning
confidence: 99%